2012
DOI: 10.1037/a0027619
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional collaboration: A survey of Canadian psychologists and psychiatrists.

Abstract: A biopsychosocial approach to mental health necessitates the integration of different perspectives into client care and requires that professionals from different disciplines be able and willing to collaborate with one another. The authors conducted an Internet survey of Canadian psychologists (n = 1,040) and psychiatrists (n = 247) about their experiences in collaboration between the two professions. The sample included both autonomous professionals and those in training. The majority of respondents described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…At the regulatory body level, Lee et al (2012) and Church et al (2009) proposed allowing supervision by other professionals to promote IPE and IPP as part of students’ and early career psychologists’ professional development. Acknowledging that this may be contentious, it would seem that if IPE is already occurring in our graduate-level health profession programs, the next logical step is to look at ways this can be expanded in the field to allow for greater interprofessional learning and collaboration.…”
Section: Call To Action: Renewed Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…At the regulatory body level, Lee et al (2012) and Church et al (2009) proposed allowing supervision by other professionals to promote IPE and IPP as part of students’ and early career psychologists’ professional development. Acknowledging that this may be contentious, it would seem that if IPE is already occurring in our graduate-level health profession programs, the next logical step is to look at ways this can be expanded in the field to allow for greater interprofessional learning and collaboration.…”
Section: Call To Action: Renewed Leadershipmentioning
confidence: 99%
“…Professions are socialized and educated to view situations through distinct lenses, which results in each profession having a unique ‘cognitive map.’ Thus, learning how to see a situation from another professional’s perspective is an important first step to successful IMHCP. The importance of having an awareness of these differing cognitive maps is underscored by the results of a survey of Canadian psychiatrists ( n = 247) and psychologists ( n = 1,040) conducted by Lee, Schneider, Bellefontaine, Davidson, and Robertson (2012). The results indicated that “over one third of respondents reported little or no familiarity with the training, assessment activities, or interventions of the other profession .…”
Section: Introductionmentioning
confidence: 99%
“…D'ailleurs, différents auteurs font état d'une « dominance médicale » (Bourgeault & Mulvale, 2006 ;Drewlo, 2014) de l'attitude négative des professionnels de santé l'un envers l'autre, la méconnaissance de l'autre et de son champ de pratique (Lee, Schneider, Bellefontaine, Davidson & Robertson, 2012), mais aussi en raison de facteurs contextuels avec les contraintes de temps et les modèles de rémunération qui ne facilitent pas la collaboration (Drewlo, 2014 (Grenier et al, 2008a) ont montré la volonté des médecins de famille de collaborer avec les psychologues, mais aussi que diverses barrières rendent la collaboration difficile ou peu satisfaisante. Les médecins de famille rapportent qu'il y a souvent une absence de rétroaction de la part des psychologues ou encore des barrières financières et même une certaine difficulté à savoir où trouver les ressources en psychologie (Grenier et al, 2008a ;Chomienne et al, 2011).…”
Section: Perspective Canadienne De La Collaboration Entre Les Médecinunclassified
“…In particular the need for interprofessional collaboration between psychologists and psychiatrists has been highlighted (Lee, Schneider, Bellefontaine, Davidson, & Robertson, 2012). More than a third of psychologists and psychiatrists surveyed by Lee and colleagues reported limited knowledge of training, assessment and interventions of the other profession.…”
Section: Introductionmentioning
confidence: 99%